2015
DOI: 10.5500/wjt.v5.i3.102
|View full text |Cite
|
Sign up to set email alerts
|

Role of steroid maintenance in sensitized kidney transplant recipients

Abstract: AIM:To evaluate whether there is a threshold sensitization level beyond which benefits of chronic steroid maintenance (CSM) emerge. METHODS: Using Organ Procurement and TransplantNetwork/United Network of Organ Sharing database, we compared the adjusted graft and patient survivals for CSM vs early steroid withdrawal (ESW) among patients who underwent deceased-donor kidney (DDK) transplantation from 2000 to 2008 who were stratified by peak-panel reactive antibody (peak-PRA) titers (0%-30%, 31%-60% and > 60%). A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Five studies reported graft loss events for both the experimental and control groups, and the other three studies reported graft loss HRs for SWA . The pooled analysis of graft loss events found no difference between the SWA and CSM groups (RR = 0.54, 95% CI 0.29‐1.00, P = 0.05).…”
Section: Resultsmentioning
confidence: 95%
See 4 more Smart Citations
“…Five studies reported graft loss events for both the experimental and control groups, and the other three studies reported graft loss HRs for SWA . The pooled analysis of graft loss events found no difference between the SWA and CSM groups (RR = 0.54, 95% CI 0.29‐1.00, P = 0.05).…”
Section: Resultsmentioning
confidence: 95%
“…A flow chart of the screening process is presented in Figure . Six studies focused on African Americans, one on repeat kidney transplantation, and one on sensitized patients . The investigators divided the sensitized population into three groups based on their PRA levels (0%‐30%, 30%‐60%, and >60%) but included data from only the latter two groups for further evaluation …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations